Antidiabetic therapy effects on bone metabolism and fracture risk. Issue 9 (24th February 2013) - Montagnani, A.; Gonnelli, S.
<x xml:space="preserve">Abstract</x> Patients with diabetes are at greater risk of fractures mostly due to not only to extraskeletal factors, such as propensity to fall, but also to bone quality alteration, which reduces bone strength. In people with diabetes, insulin deficiency and hyperglycaemia seem to play a role in determining bone formation alteration by advanced glycation end product (AGE) accumulation or AGE/RAGE (receptors for AGE) axis imbalance, which directly influence osteoblast activity. Moreover, hyperglycaemia and oxidative stress are able to negatively influence osteocalcin production and the Wnt signalling pathways with an imbalance of osteoblast/osteoclast activity leading to bone quality reduction as global effect. In addition, other factors such as insulin growth factors and peroxisome proliferator‐activated receptor‐γ pathways seem to have an important role in the pathophysiology of osteoporosis in diabetes. Although there are conflicting data in literature, adequate glycaemic control with hypoglycaemic treatment may be an important element in preventing bone tissue alterations in both type 1 and type 2 diabetes. Attention should be paid to the use of thiazolidinediones, especially in older women, because the direct negative effect on bone could exceed the positive effect of glycaemic control. Finally, preliminary data on animals and in humans suggest the hypothesis that incretins and dipeptidyl peptidase‐4 inhibitors could have a positive effect on bone metabolism by a direct effect on bone cells; however, such issue needs further investigations.